Pelatihan Hijab Style Syar’i bagi Santriwati di Pondok Pesantren untuk Meningkatkan Nilai Religiusitas - Jannah, Itayatul; Farihah, Iftahul; Rolanda, Levina Faila; Pujiati, Tri (Keris: Journal of Community Engagement, 2025)
This community service activity was carried out to improve the understanding of female students in the Islamic boarding school environment in using the hijab style according to sharia so that it can increase the religious value of the female students. The main problem faced by partners in this Islamic boarding school environment is the use of the sharia hijab which has not been optimally implemented by the students. Although the female students in the Islamic boarding school environment are accustomed to wearing the hijab, however, there is a problem with the use of the hijab which still does not use the sharia hijab. This community service activity was carried out to provide training to female students in the Islamic boarding school environment regarding the use of the sharia hijab style. The training method used to provide this sharia hijab style training uses the sharing hearing method, direct practice, question and answer, and documentation. The method used aims to train the use of a stylish sharia hijab, observe the results of the results that have been practiced, and also assess the results that have been practiced. This hijab style training activity was held on 16th October 2024 at the Nurul Amanah Islamic Boarding School, Bangkalan, Madura. The results of this hijab style training activity can increase the knowledge of female students regarding the use of syar'i hijab in accordance with Islamic teachings so that it can increase the religiosity of female students in the Islamic boarding school environment. Not only that, the results of this community service activity can be implemented in everyday life both in the Islamic boarding school environment and outside the Islamic boarding school to always use the hijab with the syar'i hijab model